Development of a Two-Layer Secure IoT Locker System Using e-KTP RFID and Mobile OTP via Blynk Platform - Ummu Handasah; Ryandika Afdila; Arman Sani; Rizky Hendrawan; Muhammadin Hamid (Talenta Publisher, 2025)
The growing demand for safe storage in public places has highlighted the flaws of single-factor authentication methods such as RFID, which are vulnerable to cloning. This study solves these security weaknesses by building and implementing a safe, low-cost IoT locker with a strong two-factor authentication (2FA) mechanism. The suggested method combines Indonesia's national ID card (e-KTP) for initial RFID-based access with a dynamic One-Time Password (OTP) sent to the user's smartphone via the Blynk IoT platform. The NodeMCU ESP8266-based prototype underwent extensive reliability, performance, and security testing. The results showed that both e-KTP and OTP validation were 100% accurate. The performance research revealed an average OTP delivery time of 5.6 seconds and a total access time of 28.2 seconds. Crucially, security analysis confirmed that the required second factor (OTP) effectively prevented unauthorized access even when the e-KTP was cloned. This study confirms a realistic and scalable two-factor authentication system that considerably increases locker security over single-factor techniques.